Urban mobil 2003 - Fister, Peter (AR. Arhitektura, raziskave, 2004)
The result of the WP4 (Architecture and urban structures) in the first phase of the Re Urban project is based on a collection and survey of European and global practice that was also the basis for developing theoretical and methodological tools. Most of the direct novelties and experiences came from detailed field work on selected case studies in Ljubljana, which will be proposed and discussed alongside other case studies at the beginning of the second phase with other work package leaders. Dissemination of results was carried out in Slovenia (on the national and city level and among inhabitants) and some encouraging results were achieved. Some new methods of documentation and analyses of built structures were developed that could become part of a comprehensive reurbanisation methodology.
Keywords: architecture; arhitektura; urbanism; urbanizem; arhitekturna dediščina; varstvo; razvoj; Slovenia; Slovenija; raziskave